Brain-enriched MicroRNA-184 is downregulated in older adults with major depressive disorder: A translational study. (April 2019) - Mendes-Silva, Ana Paula; Fujimura, Patricia Tiemi; Silva, Jéssica Regina da Costa; Teixeira, Antonio Lucio; Vieira, Erica Marciano; Guedes, Pedro Henrique Gonçalves; Barroso, Lucélia Scarabeli Silva; Nicolau, Mariana de Souza; Ferreira, Jéssica Diniz Rodrigues; Bertola, Laiss; Nicolau, Eduardo de Souza; Tolentino-Araújo, Gesiane Thamire; et al.
Abstract: Changes in microRNAs (miRNAs) expression have been described in major depressive disorder in young and middle-aged adults. However, no study has evaluated miRNA expression in older adults with major depression (or late-life depression [LLD]). Our primary aim was to evaluate the expression of miRNAs in subjects with LLD. We first evaluated the miRNA expression using next-generation sequencing (NGS) and then we validated the miRNAs found in NGS in an independent sample of LLD patients, using RT-qPCR. Drosophila melanogaster model was used to evaluate the impact of changes in miRNA expression on behavior. NGS analysis showed that hsa-miR-184 (log2 foldchange = −4.21, p  = 1.2 × 10 −03 ) and hsa-miR-1-3p (log2 foldchange = −3.45, p  = 1.3 × 10 −02 ) were significantly downregulated in LLD compared to the control group. RT-qPCR validated the downregulation of hsa-miR-184 (p < 0.001), but not for the hsa-miR-1-3p. The knockout flies of the ortholog of hsa-miR-184 showed significantly reduced locomotor activity at 21–24 d.p.e (p = 0.04) and worse memory retention at 21–24 d.p.e (24h post-stimulus, p = 0.02) compared to control flies. Our results demonstrated that subjects with LLD have significant downregulation of hsa-miR-184. Moreover, the knockout of hsa-miR-184 in flies lead to depressive-like behaviors, being more pronounce in older flies. Highlights: Late-life depression is complex and heterogeneous disorder. Abnormalities in microRNA expression may play a role in its pathophysiology mechanism. Next generation RNA sequencing showed a significant downregulation of mir-184 in late-life depression. Flies with knocked-out of mir-184 showed a decreased locomotor activity and worse memory retention, more significant at older ages. Downregulation of mir-184 may be linked to the development of depression and cognitive impairment in the elderly.